On the Hardy-Littlewood Maximal Operator in Zorko Spaces - Dahliatul Hasanah; Sisworo Sisworo; Ariska Nurfitriyani Rahmawati (JMPM: Jurnal Matematika dan Pendidikan Matematika, 2026)
Zorko spaces are introduced to address the density issue in Morrey spaces which are defined by utilizing the difference of a function of first order. Later the difference of a function of second order is also employed to define modified Zorko spaces and approximation properties are investigated therein. On the other hand, integral operators are mostly studied on the boundedness properties in Morrey spaces and its variants. In this paper, integral operators, especially Hardy-Littlewood maximal operators and fractional Hardy-Littlewood maximal operators, are investigated its boundedness and closedness properties in Zorko spaces.